Membuka Mata Melalui Nilai Pendidikan Moral Dalam Tari Trilogi Jailolo Karya Eko Supriyanto - Vindsey Wijaya, Gemma Arzetta; Widiyastuti, Asyidah Kharisma (Universitas Negeri Surabaya, 2024)
This study examines the form and implementation of moral value education in the Trilogy Jailolo, a performance art series by Eko Supriyanto. The research aims to describe the moral values embedded in the Trilogy Jailolo and their potential role in education. Employing a qualitative method with a library research approach, the study analyzes data through interviews and descriptive analysis to generate written observations. The findings indicate that moral value education can be effectively conveyed through performance art. The three works in the Trilogy Jailolo—each inspired by the real-life experiences of the people of Jailolo, West Halmahera—highlight diverse moral values that serve as important references for moral education in both local and broader societal contexts. These works emphasize themes of cultural preservation, community resilience, and harmony, illustrating the capacity of art to address ethical principles and social responsibility. The study underscores that moral value education need not be confined to formal educational settings. Performance art, such as the Trilogy Jailolo, offers a meaningful medium to engage audiences and foster deeper understanding of moral principles. This research contributes to the discourse on integrating arts into educational frameworks, highlighting how creative expression can enhance moral development and cultural awareness. By analyzing the Trilogy Jailolo, this study provides insights into the intersection of performance art and moral education, offering practical implications for educators and cultural practitioners. Further research could explore similar applications in other cultural and artistic contexts.